Evidence Versus Practice: Operative Treatment Preferences in Hallux Valgus. Issue 4 (12th December 2018) - Noback, Peter C.; Trofa, David P.; Vosseller, J. Turner
Background: There is substantial variability in the operative treatment of hallux valgus despite the existence of high quality evidence to guide treatment decisions. The purpose of this study was to determine the current trends in the treatment of mild, moderate, and severe hallux valgus and if greater degrees of consensus correlate with the presence of higher-level evidence. Methods: Members of the American Orthopaedic Foot & Ankle Society completed a 14-item survey. A total of 131 (14%) of 922 members completed the survey. Three cases representing 3 stages of HV were presented, and respondents selected their preferred treatment. Preferred forms of proximal and distal metatarsal osteotomies, as well as mode of fixation for each, were inquired. Results: In the treatment of mild hallux valgus without second metatarsalgia, 80% of those surveyed chose a distal metatarsal osteotomy, while, if second metatarsalgia was present, 56% chose a distal metatarsal osteotomy with a second metatarsal-shortening osteotomy. In the treatment of moderate hallux valgus, there was generally less consensus, while, in the treatment of severe hallux valgus, a majority of those surveyed chose a Lapidus procedure, with the addition of a second metatarsal-shortening osteotomy in the presence of second metatarsalgia. The most popular distal and proximal metatarsal osteotomies, respectively, were chevron osteotomy (80%) and opening wedge osteotomy (33%). The presence of Level I evidence did not significantly correlate with higher degrees of consensus. Conclusion: Despite the existence of high-quality evidence supporting the use of certain procedures in the treatment of HV, there exists an apparent lack of consensus among surgeons about the choice of surgical procedures. Moreover, higher-level evidence was not correlated with greater consensus in hallux valgus. Level of Evidence: Level II.